2017
DOI: 10.1111/beer.12174
|View full text |Cite
|
Sign up to set email alerts
|

The performance of socially responsible equity mutual funds: Evidence from Sweden

Abstract: This paper presents a comprehensive analysis of socially responsible (SR) funds in Sweden by assessing fund managers' abilities and performances across different market states. These issues are analyzed at the aggregate and individual fund levels. The paper also presents several new statistical tests that allow more precise inferences about differences in performance and the variability in fund returns arising from different benchmarks. In general, SR and conventional funds perform similarly to the market. At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 90 publications
2
16
0
Order By: Relevance
“…For the other analyzed countries, no significant relationship is noted between screening and fund performance. The same results are obtained by Leite et al [44] for 33 Swedish SRI funds from November 2002 to October 2012. Moreover, authors classify analyzed funds into three groups according to their geographic focus of investment: funds investing in Sweden, in Europe, and globally.…”
Section: Hypothesis 3 (H3)supporting
confidence: 87%
See 2 more Smart Citations
“…For the other analyzed countries, no significant relationship is noted between screening and fund performance. The same results are obtained by Leite et al [44] for 33 Swedish SRI funds from November 2002 to October 2012. Moreover, authors classify analyzed funds into three groups according to their geographic focus of investment: funds investing in Sweden, in Europe, and globally.…”
Section: Hypothesis 3 (H3)supporting
confidence: 87%
“…The above assumption leads to the conclusion that it is appropriate to use an equal-weighted portfolio return when assessing a fund's performance. In addition, it should be noted that a similar approach was presented both in earlier groundbreaking papers connected with socially responsible investment [52] and in the latest empirical research [30,44,53,54]. However, it is more practical to use a value-weighted portfolio return to examine the fund portfolio structure and its impact on investment results [51,[55][56][57].…”
Section: Data and Portfolio Constructionmentioning
confidence: 98%
See 1 more Smart Citation
“…These findings are in line with most previous studies that reported that SRI performs similarly to conventional investments. Most empirical studies on the performance of SRI mutual funds across different geographical areas found no significant differences between their performance and that of conventional funds [5,50]. Likewise, many empirical studies evaluating differences between high and low-ranked firms, according to their CSR scores, also found that the differences are not significant [2,28].…”
Section: Discussionmentioning
confidence: 99%
“…The resulting alpha was the estimated financial portfolio performance. This approach was commonly used in previous related studies [49,50]. A challenge in the evaluation of financial performance is the need for controlling alternative explanations.…”
Section: Robustness Checksmentioning
confidence: 99%